Ülevaade eestlastest Ameerika Ühendriikide relvajõududes pärast Teist maailmasõda [Estonians in the U. S. Armed Forces after World War II: An overview] - Luts, Kristjan (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2011)
After the end of World War II the victorious allies faced numerous problems and difficulties in post-war Europe. Among others were the millions of war refugees and thousands of ex-servicemen who had served in the German armed forces during the war and had now been taken prisoners of war. Almost a quarter of the people in Germany and Austria, for example, were refugees: even in 1947 the United States still had custody of 47,396 displaced persons in Austria alone, of which 90 percent were deemed ‘irrepatriatable’ because of the political situation in Eastern Europe. In the eyes of many Europeans, these groups were little more than sources of disease and crime. They were seen as competitors for scarce housing and jobs and as potential recruits for future demagogues who might trigger another European conflict. To enhance the stability of fragile post-war states, it was essential to resolve the status of Europe’s stateless populations as quickly as possible. The western allies, however, did not have a clear concept of what to do about the East-European nationals who generally refused to return to their home country. Thus various options were implemented: it was rather common that officials responsible for the screening process acted according to their own standpoints, political beliefs and in some cases also the luck of draw. Especially in the French zone there were cases when refugees were handed over to the Soviet representatives and sent back ‘home’ by force.